Synthesis, structural characterization and anti-carcinogenic activity of new cyclotriphosphazenes containing dioxybiphenyl and chalcone groups - Görgülü, Ahmet Orhan; Koran, Kenan; Özen, Furkan; Tekin, Suat; Sandal, Süleyman (My University, 2015)
2,2-Dichloro-4,4,6,6-bis[spiro(2?,2?-dioxy-1?,1?-biphenylyl]cyclotriphosphazene (2) was synthesized from hexachlorocyclotriphosphazene (HCCP) and 2,2?-dihydroxybiphenyl. The mixed substituent chalcone/dioxybiphenyl cyclophosphazenes (2a–h) were obtained from the reactions of (2) with hydroxy chalcone compounds in K2CO3/acetone system. The chalcone-cyclophosphazene compounds were characterized by elemental analysis, FT-IR, 1H, 13C, 31P NMR techniques. In vitro anti-carcinogenic activities of all compounds were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Anti-carcinogenic activity of the compounds (2a–h) against androgen-dependent (LNCaP) and independent (PC-3) human prostate cancer cell lines were investigated. Our results indicate that the chalcone-phosphazene compounds (2a–h) have anti-carcinogenic activity on PC-3 and LNCaP cell lines (p < 0.05). The effective dose of the compounds was determined as 100 ?M.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Cyclotriphosphazene; Chalcone-phosphazenes; Anti-carcinogenic activity; PC-3 and LNCaP